Divergent BLA engram circuits orchestrate social preference dynamics in bystander male mice with self-experienced stress - Xue-Ke Yang; Yu-Long Shi; Ming Li; Tong-Xia Li; Jian Yang; Jie Lei; Chi Cui; Xiang Peng; Hong-Chu Zha; Gan-Gan Luo; Yi-Bo Yao; Si-Tong Chen; et al. (Proceedings of the National Academy of Sciences, 2026)
Personal experiences are encoded and stored in memory engram cells and are crucial for social preference dynamics in future social contexts, yet the neural circuit mechanisms involved are still poorly understood. Here, we develop a mouse model that combines self-experienced single social defeat stress with vicarious social defeat stress, demonstrating a social preference with defeat stress-experienced cagemate and social avoidance toward an aggressor. Basolateral amygdala engram cells (BLA EC ) exhibit significant activation, and chemogenetic manipulations confirm their sufficiency and necessity for both social preference and social avoidance behaviors. Virus-based cell-type-specific brain mapping suggests BLA EC project to anterior cingulate cortex (ACC) and these projections are also responsible for modulating social preference dynamics. Distinct projections from BLA-ACC circuit, including ventral/dorsal hippocampus and zona incerta, exert the diverse effects on these behaviors in male mice. Our findings reveal regulation of social preference dynamics by divergent circuits originating from BLA EC , which may contribute to the neurobiological mechanism of social psychopathologies.